Comunidades de práticas na internet: um estudo de duas comunidades hospedadas em portais públicos brasileiros - Affonso, Luiz Carlos (2012)
This dissertation investigates the interaction and learning processes that occur in virtual communities of practice, with emphasis given to experiences hosted in Brazilian public portals. To better understand these experiences one considers here the general characteristics and evolution of some outstanding initiatives of electronic government in Brazil. One also considers theoretical approaches to the following basic concepts: community, social network, virtual community and virtual social network, virtual communities of practice. Specificities, advantages and problems involved in the creation and maintenance of virtual communities of practice, according to experts, are taken into consideration in an online questionnaire applied to the members of two virtual communities: The Amadeus community hosted in the Brazilian Portal de Software Público and the community called Comitê Técnico de Gestão do Conhecimento e Informação Estratégica (CT-GCIE) hosted in the Portal das Comunidades Virtuais do Setor Público. Results obtained from data analysis developed here, systematically comparing the two communities, indicate that they are active and seem to contribute to their member s professional development. Results, including suggestions given by respondents, also point out to some problems faced by the communities studies and provide some ideas to those interested in creating, participating and in keeping alive an online community of practice